2016
DOI: 10.1002/uog.14881
|View full text |Cite
|
Sign up to set email alerts
|

Association between fetal growth, cerebral blood flow and neurodevelopmental outcome in univentricular fetuses

Abstract: Objective To investigate the association of fetal growth and cerebrovascular resistance at different periods in gestation with neurodevelopment (ND) at 14 months in the univentricular subject. Methods We reviewed serial prenatal ultrasound (US) examinations from 133 infants enrolled in the Pediatric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 19 publications
7
73
1
Order By: Relevance
“…This finding has also been reported in an MRI study in TOF fetuses [22]. The hypothesis that the specific type of heart defect, such as HLHS and TOF, might play an important role in fetal cerebral development has been suggested in an increasing number of studies [10, 13, 26, 28, 29]. When specific types of CHD are studied in depth, it was furthermore found that neonates with minor CHD such as ventricular septal defects also demonstrate altered brain growth [30], which was the rationale for us to include minor CHD in our current study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This finding has also been reported in an MRI study in TOF fetuses [22]. The hypothesis that the specific type of heart defect, such as HLHS and TOF, might play an important role in fetal cerebral development has been suggested in an increasing number of studies [10, 13, 26, 28, 29]. When specific types of CHD are studied in depth, it was furthermore found that neonates with minor CHD such as ventricular septal defects also demonstrate altered brain growth [30], which was the rationale for us to include minor CHD in our current study.…”
Section: Discussionsupporting
confidence: 54%
“…The prenatal studies are, however, dominated by a series of severe CHD and left-sided CHD [13, 16, 17], and some studies also included cases with non-isolated CHD [18, 19]. The reported variables, such as head circumference and flow indices, are very heterogeneous and were assessed at different gestational ages (GAs) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced fetal CVR was initially shown to be associated with lower cognitive scores at 18 months of age in a small cohort of mixed complex CHD 96 . However, two studies with larger and more homogeneous populations of univentricular fetuses demonstrated that decreased CVR, determined by the middle cerebral artery pulsality index, is associated with higher neurodevelopmental scores at 14 months of age determined by the Pyschomotor Development Index 39, 97 . Together, these clinical studies indicate that hemodynamics should be carefully monitored during fetal development and that optimizing cerebral oxygen delivery may improve neurodevelopmental outcomes in specific CHDs.…”
Section: Risk Factors Associated With Chdmentioning
confidence: 98%
“…It has been assumed that prolonged periods of this autoregulation may lead to delayed maturation of the fetal oligodendrocytes, reduced myelinization, and increased vulnerability of the brain (2528). However, in fetuses with single ventricular heart, decreased cerebrovascular resistance has been found associated with higher PDI scores at the age of 14 months (29, 30). It remains unclear whether fetal cerebral blood flow alterations predict ND outcomes later in childhood.…”
Section: Encephalopathy Of Chd: Delayed Maturation Injury and Neuromentioning
confidence: 99%